FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA MINAT TERHADAP KONTRASEPSI INTRAUTERINE DEVICE DI BPM KERTAPATI - Maria Ostradela; Minarti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Intra Uterine Device is a contraceptive that is placed in a vacuum to block fertility and makesit difficult for the eggs to implant in the uterus. Globally, users of modern contraception haveincreased from 54% in 1990 to 57.4% in 2014. of this study was to determine the factorsassociated with the low interest in Intarauterine Device contraception in BPM SundariKertapati in 2019. This study used an analytical survey research method with a cross sectionalresearch design. Sampling was carried out using accidental sampling obtained as many as 81acceptors. The instrument used was a questionnaire. by using the chi square test analysisshowed the results there was a significant relationship between the role of health workers tothe low interest of IUDs with p = 0,000, there was a significant relationship between maternalknowledge of the low interest of IUDs with p = 0,000, there was a significant relationshipbetween encouragement husband's low interest in IUD with p = 0,000. It is hoped that healthworkers will improve people's understanding by approaching and changing people's attitudeswith false myths about IUDs. Improve acceptor knowledge education about the effectiveness,advantages and disadvantages of IUD contraception. Educating the husband to support hiswife using an IUD with an approach, counseling and socialization about IUD contraception.